FOAM SCLEROTHERAPY IN THE TREATMENT OF AXIAL VS COLLATERAL VARICOSITIES. - Kar, Himadri Sekhar; Pachal, Sumitava (Student's Journal of Health Research Africa, 2023)
Introduction: Varicose veins are one of the most common distressing situations, affecting almost 30-50% of the adult population. Patients experience throbbing pain, heaviness of the limb, bleeding on trivial trauma, and even ulceration. There are many treatment modalities like compression stocking, radiofrequency ablation, sclerotherapy, and open surgical treatment. Among them, ultrasound-guided sclerotherapy has been a widely accepted procedure. It is simple, minimally invasive, and allows patients to return to their baseline activity level quickly. Foam sclerotherapy is the newest addition. Here air is mixed with the liquid sclerosant to create the “foam”, which is injected into the vein under ultrasound guidance. Aims and Objectives: To compare the effectiveness of foam sclerotherapy in treating axial and collateral varicosities. Methods: This study was conducted between August 2020 and July 2022 in Midnapore Medical College and Hospital. 100 patients having varicosity of the lower limb were divided into two groups of 50 patients each: patients having Axial varicosity and Collateral varicosity. Both the groups were treated with foam sclerotherapy and a serial ultrasound was obtained on the 2nd week, 1st month, 6th month, 12th month, and 24th month to see the effectiveness. Result: The p-value was statistically insignificant, which implied that there was no significant difference in the outcome of treatment of both axial and collateral varicosities by foam sclerotherapy. Conclusion: Foam sclerotherapy is equally effective in treating both axial as well as collateral varicosities. Recommendation: To increase the general safety of foam sclerotherapy injection of very viscous foam in the varicose veins should be considered. Also, the patient should not move, specifically their leg for several minutes, and also should not carry out the Valsalva maneuver.